Use of Mitomycin C for Refractory Esophageal Stricture following Tracheoesophageal Fistula Repair - Lakoma, Anna; Fallon, Sara C.; Mathur, Shawn; Kim, Eugene S. (European Journal of Pediatric Surgery Reports, 2013)
Esophageal stricture is a well-described complication following tracheoesophageal fistula repair. Herein, we report two patients who had persistent esophageal strictures after several months of repeat balloon dilatations. Each patient was treated with a single application of topical mitomycin C in addition to esophageal dilatation, which resulted in complete resolution of the stricture.
Keywords: mitomycin C; esophageal stricture; tracheoesophageal fistula